2021
DOI: 10.1111/ijfs.15449
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, sensorial and microcosmic properties of Chinese dried noodles fortified with unhulled and hulled flaxseed flour

Abstract: Chinese dried noodles (CHDNs) were fortified with unhulled flaxseed flour (UHFF) and hulled flaxseed flour (HFF), and textures, antioxidant activities, sensory properties and microstructure were investigated. The optimal levels of UHFF and HFF added to CHDNs were 5% and 10%, respectively. Compared with HFF, UHFF addition enhanced the in vitro antioxidant activities but significantly decreased the colour of CHDNs. The addition of UHFF and HFF increased the cooking loss and decreased the hardness, firmness force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…Removing the peel from flaxseed could reduce the level of strong odors formed during processing, which was attributed to the removal of chemically reactive substances (Yang et al., 2021). Researchers have investigated the effects of dehulled and hulled flaxseed on the properties of Chinese dried noodles, and found that dehulling greatly decreased their roughness (Duan et al., 2021). However, the peeling process was complicated and greatly increased the production cost.…”
Section: Pretreatment Of Flaxseed Before Incorporation Into Foodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Removing the peel from flaxseed could reduce the level of strong odors formed during processing, which was attributed to the removal of chemically reactive substances (Yang et al., 2021). Researchers have investigated the effects of dehulled and hulled flaxseed on the properties of Chinese dried noodles, and found that dehulling greatly decreased their roughness (Duan et al., 2021). However, the peeling process was complicated and greatly increased the production cost.…”
Section: Pretreatment Of Flaxseed Before Incorporation Into Foodsmentioning
confidence: 99%
“…However, there are challenges to incorporate whole flaxseed (flour) into food products owing to the presence of antinutritional factors, the oxidation of unsaturated lipids, the unique flavor profile, the hard texture, and the partial digestive barriers (Bekhit et al., 2018; Duan et al., 2021; Marambe et al., 2013; Zajac et al., 2017). Processing, such as heating, peeling, fermentation, and size reduction are necessarily used to improve the functionality and sensory attributes of whole flaxseed (flour).…”
Section: Introductionmentioning
confidence: 99%
“…The CHDNs were prepared following the method described by Duan et al . (2022). Salt (2.0 g per 100 g) and water (40 ± 2 mL) were mixed to make a dough.…”
Section: Methodsmentioning
confidence: 99%
“…A number of researches have been carried out to prepare noodles by adding untreated flaxseed flour at varying levels 12‐15 . However, there is no information in the literature about the impact of dephytinized flaxseed flour on the noodle quality.…”
Section: Introductionmentioning
confidence: 99%
“…A number of researches have been carried out to prepare noodles by adding untreated flaxseed flour at varying levels. [12][13][14][15] However, there is no information in the literature about the impact of dephytinized flaxseed flour on the noodle quality. Therefore, the aims of this study were (i) to reduce the phytic acid concentration of flaxseed flour through phytase enzyme treatment and baker's yeast fermentation, (ii) to examine the impacts of dephytinization methods on the color, proximate composition, phytic acid content and antioxidant activity of flaxseed flour, (iii) to produce functional noodles by adding untreated and dephytinized flaxseed flours at 10%, 20% and 30% levels, (iv) to determine the color, cooking quality, texture, chemical and sensory properties of noodles made from untreated and dephytinized flaxseed flours and (v) to compare the mentioned characteristics of flaxseed noodles with each other and 100% wheat noodle.…”
Section: Introductionmentioning
confidence: 99%